Developing Aqidah Akhak As Islamic Elementary School Teaching Material Supplement Based On Religious Moderation Values - Arifin, Siful (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2024)
Efforts must be made to instill in young people the values of religious moderation in order to prevent the spread of increasingly radical ideas that affect all segments of society, including children. Consequently, it is critical that educational institutions at every level incorporate the values of religious moderation into at least one course of study as a preventative measure. One potential approach is to incorporate or supplement teaching materials with values associated with religious moderation as the case with the investigation and creation of this particular instructional resource. This research aims: 1) to develop Aqidah Akhlak as Islamic Elementary School teaching material based on religious moderation; 2) to determine the suitability of teaching materials that have been developed according to expert judgment and students at MIN 1 Sumenep. This research used the Borg and Gall model research and development method. The research subjects consisted of 20 students of class VI MIN 1 Sumenep. The data collection techniques used were questionnaires (quantitative), interviews, documentation, and note sheets of comments/recommendations from validators/experts (qualitative). Data analysis used quantitative and qualitative. Based on expert validation and field trials, the Aqidah Akhlak as Islamic Elementary School teaching material based on religious moderation development product based on the values of religious moderation is suitable to be used as a supplement to the moral aqidah textbook in class VI of MIN Sumenep and to be disseminated widely.